The effect of profitability on stock prices in transportation companies listed on the indonesian stock exchange - Ulfa Natalia; Aswin Akbar (SEAN Institute, 2024)
The purpose of this study was to analyze the effect of the profitability of the stock prices of transportation companies listed on the Indonesia Stock Exchange affecting stock price fluctuations between 2020 and 2022. Therefore, researchers wanted to find out whether return on assets, return on equity, earnings per share would affect changes stock price. In this case the researcher chose the ratio of ROA, ROE, and EPS as a measure of profitability. The data used are secondary and quantitative data. The population used in this study are transportation companies for the 2020-2022 period. The sample for this survey is 10 companies. Data management techniques use partial testing (T), simultaneous testing (F), and using the SPSS version 23 software application to manage the data. The results of this study indicate that return on assets has no partial effect on stock prices with a significant value of 0.269> 0.05, return on equity has a partial effect on stock prices with a significant value of 0.019 <0.05, Earning per share has a partial effect on share price with a significant value of 0.002 <0.005. Simultaneously return on assets, return on equity, and earnings per share affect stock prices.